La intertextualidad como característica esencial del discurso publicitario - López Mora, Pilar (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Any text is shaped by traces of other texts. The concept of intertextuality is one of qualities of the language of advertisement. Advertisement imitates, parodies, synthesizes every possible language. This is an incursion to advertising speech as an intertext that reminds of daily speech, journalistic, literary, and cinematographic speech, not forgetting the fact that often the cross-referencing is made to more than one text and in several semiotics codes.
Keywords: Advertisement language; intertextuality; pragmatics; discourse analysis